Ultrathin Planar Cavity Metasurfaces. Issue 17 (3rd April 2018) - Wang, Hsiang‐Chu; Chu, Cheng Hung; Wu, Pin Chieh; Hsiao, Hui‐Hsin; Wu, Hui Jun; Chen, Jia‐Wern; Lee, Wei Hou; Lai, Yi‐Chieh; Huang, Yao‐Wei; Tseng, Ming Lun; Chang, Shu‐Wei; Tsai, Din Ping
Abstract: An ultrathin planar cavity metasurface is proposed based on ultrathin film interference and its practicability for light manipulation in visible region is experimentally demonstrated. Phase of reflected light is modulated by finely adjusting the thickness of amorphous silicon (a‐Si) by a few nanometers on an aluminum (Al) substrate via nontrivial phase shifts at the interfaces and interference of multireflections generated from the planar cavity. A phase shift of π, the basic requirement for two‐level phase metasurface systems, can be accomplished with an 8 nm thick difference. For proof of concept, gradient metasurfaces for beam deflection, Fresnel zone plate metalens for light focusing, and metaholograms for image reconstruction are presented, demonstrating polarization‐independent and broadband characteristics. This novel mechanism for phase modulation with ultrathin planar cavity provides diverse routes to construct advanced flat optical devices with versatile applications. Abstract : An ultrathin planar cavity metasurface based on ultrathin film interference is reported. A phase shift of π can be accomplished with an 8 nm thick difference of amorphous silicon. For proof of concept, gradient metasurfaces for beam deflection, Fresnel zone plate metalens for light focusing, and metaholograms for image reconstruction are demonstrated in the visible spectrum.